Pengaruh Kompetensi Pedagogik Dan Motivasi Ekstrinsik Terhadap Kinerja Guru: Studi Kasus Pada Salah Satu Sekolah Dasar Negeri di Kota Bandung - Diana Firmansyah; Farid Riadi; Ujang Wawan Sam Adinata; Asep Rochyadi Suherman (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study was conducted with the aim to determine the effect of pedagogic competence and extrinsic motivation on performance and this study also aims to analyze the most dominant factor influencing pedagogic competence and extrinsic motivation on teacher performance. This research method uses descriptive and verification methods in pedagogic competence and extrinsic motivation on teacher performance in an effort to obtain data and information that will support this research by taking the object of research as many as 30 teachers using a questionnaire aimed at teachers at one of the State Elementary Schools. in the city of Bandung. Based on the results of research using path analysis, it can be seen that the pedagogic competence variable (X1) has a direct influence of 25.9%, an indirect effect through the relationship of extrinsic motivation (X2) of 16.1%, and a total effect of 42%. Extrinsic motivation (X2) has a direct effect of 17.9% and an indirect effect through pedagogic competence (X1) of 16.1%, a total effect of 34%. The results of the correlation coefficient of determination (Rsquare) expressed in percentages describe the magnitude of the contribution of all independent variables, namely pedagogic competence (X1), and extrinsic motivation (X2) in determining the teacher performance variable, which is 0.760 or 76% while other factors that do not affect performance do not. studied is indicated by the value of = 0.240 or 24%. The conclusions and suggestions obtained are considered in connection with the results of the study, namely that management should be able to maintain and improve the two variables above.